Rapid screening and quantitation of PAHs in water and complex sample matrices by solid‐phase microextraction coupled to capillary atmospheric pressure photoionization‐mass spectrometry. (25th September 2020) - Mirabelli, Mario F.; Zenobi, Renato
Abstract: A capillary atmospheric pressure photoionization (cAPPI) source was used to analyze polycyclic aromatic hydrocarbons (PAHs) in complex matrices like grilled meat extract and urban dust reference material, as well as screening for PAHs in aqueous samples such as tap and lake water. A high‐throughput workflow was developed that allowed rapid screening of unknown samples by direct solid‐phase microextraction (SPME) coupled with cAPPI‐MS, with confirmatory gas chromatography performed only for samples containing trace amounts of PAHs. Extraction times were as low as 15 s, with a total analysis time of 2 min per sample for screening. Limits of detections were in the low pg/ml range and in the subpg/ml range for the direct and chromatographic approach, respectively, with a linear dynamic range between two and three orders of magnitude, as determined for 15 model PAHs. This rapid approach represents an attractive way to screen samples containing nonpolar compounds using an ambient ionization source.